Cultural Management to the Concept of Creative Cultural Tourism - Somchai, Suvimon; Phumsaen, Pikul; Arthakun , Samrej; Singmart, Sanook (Interdisciplinary Academic and Research Journal, 2023)
Background and aim: The evolution of creative cultural tourism is intricately linked to the adept application of theories, principles, concepts, practices, and knowledge pertinent to a specific subject. The successful implementation of cultural management strategies involves adapting these elements to the contextual nuances of the surroundings. This integration, in turn, catalyzes the advancement of creative cultural tourism—a form of travel intricately tied to the exploration of history, arts, culture, community traditions, and the distinctive attributes of places. It transcends the conventional tourist experience by fostering direct engagement with the custodians of the culture, thereby imparting added value to the historical, artistic, and cultural dimensions of a locale. Unlike ventures solely geared towards community income, creative cultural tourism prioritizes the preservation and celebration of community values. In essence, it serves as a bridge between tourists and the rich tapestry of a community's heritage, contributing not only to economic development but also to the perpetuation of intrinsic cultural worth. Methodology: This study used document analysis and related research methods. Analyze the content and present it descriptively according to the study objectives. Results: present cultural management leading to the development of creative cultural tourism, which stakeholders can implement to affect the national economic development at a low cost. the most The author analyzed 4 issues as follows: (1) rehabilitation issues to deal with lost or degraded cultures so that they can be restored to their original condition, (2) conservation issues to preserve the existing culture, no matter what type of culture, for as long as possible and be able to use it to the greatest benefit, (3) the issue of promotion and support is to give importance and expand the scope of the project or activity to be of better quality and completeness, (4) the issue of cultural application It is taking something related to existing culture and using it by adapting it appropriately to the current conditions, whether it is changed in culture, traditions, society, ideas or technology. Conclusion: Cultural management leads to the development of creative cultural tourism that stakeholders can use to influence national economic development. In the analysis, there are 4 important issues: restoration, conservation, promotion, and support. and application of culture It emphasizes preserving, promoting, and adapting existing culture to create benefits and enhance cultural tourism that benefits both the community and the country in the long run.